Peran Emosi Positif Pada Guru Slb Tunagrahita - Dhurul Khoiriyah; Nuristighfari Masri Khaerani (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
The purpose of this research is understanding how positive emotion on extraordinary teachers. Subjects consist of three extraordinary school teachers who already taught more than one year. This research used qualitative methods with phenomenological approach. Data collection in this research used observation and interview. This research used interactive analysis of Miles and Huberman's. The results of this research show that positive emotions generate motivation to provide services for children with special needs. Factors affecting the positive emotions that become the new findings in this research are patience and spirituality. Positive emotions make people more open to new experiences that expand the personal resources, both cognitive, social, and physical resources. Key words: positive emotions, special education, teachers